2007
DOI: 10.1017/s0022112007008610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prandtl number and a new instability mode in a plane thermal plume

Abstract: The effect of Prandtl number on the linear stability of a plane thermal plume is analyzed under quasi-parallel approximation. At large Prandtl numbers (P r > 100), we found that there is an additional unstable loop whose size increases with increasing P r. The origin of this new instability mode is shown to be tied to the coupling of the momentum and thermal perturbation equations. Analyses of the perturbation kinetic energy and thermal energy suggest that the buoyancy force is the main source of perturbation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…It can also not be ruled out that nonlinear effects alter the threshold of global instability (Couairon & Chomaz 1997). The influence of the Prandtl number has not been investigated in this study, but it has been shown by Lakkaraju & Alam (2007) that the instability behaviour of planar plumes undergoes qualitative changes as P r is varied far from unity.…”
Section: Discussionmentioning
confidence: 92%
“…It can also not be ruled out that nonlinear effects alter the threshold of global instability (Couairon & Chomaz 1997). The influence of the Prandtl number has not been investigated in this study, but it has been shown by Lakkaraju & Alam (2007) that the instability behaviour of planar plumes undergoes qualitative changes as P r is varied far from unity.…”
Section: Discussionmentioning
confidence: 92%
“…where σ k denotes the turbulent Prandtl coefficient in the kinetic equation k [35]; σ ε is the turbulent Prandtl coefficient of dissipation rate in the ε equation; µ t is the turbulence viscosity; G k is the turbulence kinetics generated from the average speed gradient; and G b is the turbulence kinetics generated from buoyancy. Furthermore,…”
Section: Of 16mentioning
confidence: 99%
“… Typical values of Pr are ∼ 10 − 2 for liquid metals, ∼ 1 for air, ∼ 10 for water, and ∼ 10 21 for Earth's mantle .…”
mentioning
confidence: 99%
“…§ Typical values of Pr are 10 2 for liquid metals, 1 for air, 10 for water, and 10 21 for Earth's mantle[24].Copyright © 2013 John Wiley & Sons, Ltd. Int. J. Numer.…”
mentioning
confidence: 99%